Uncommon association between vascular Ehlers–Danlos syndrome and ocular complications - Cherecheanu, Matei Popa; Romanitan, Mihaela Oana; Pirvulescu, Ruxandra; Iancu, Raluca; Garhöfer, Gerhard; Iancu, George; Cherecheanu, Alina Popa; Zemba, Mihail; Vasile, Victor; Simonov, Andrei; Branisteanu, Daniel (Frontiers in Medicine, 2023)
Ehlers-Danlos syndromes (EDS) represent a group of rare inherited disorders that affect connective tissues. There are 13 types of disease, most of them affecting joints or skin; symptoms usually include loose joints, joint pain, stretchy velvety skin, abnormal scar formation. However, the most serious type of disease is vascular EDS (vEDS), or EDS type 4 because patients may suffer vessels dissections or internal organs lesions, followed by bleeding, which endangers patient’s life, but also thromboembolic events. We present two clinical cases of vEDS managed in our clinic in 1 year distance. In both cases, patients were active young persons (in their thirties, and respectively, twenties), both with multiple non-traumatic vascular dissections, and severe ocular complications: arterio-venous fistula with massive exophthalmia, and central retinal artery occlusion, respectively. Both cases were challenging since the life of the patients were threatened by their condition. However, in both cases, prompt treatment and finding the right trigger of the ocular pathology and vascular injuries helped doctors to provide proper and prompt medical care, in order to prevent future similar events to happen and to preserve a good quality of life for these patients.